Psychological wellbeing and its associated factors among older adults attending daycare centers in Kathmandu, Nepal: A cross-sectional study - Rekha Timalsina; Madhusudan Subedi; Nima Maharjan; Bigya Shah; Pabitra Adhikari (PLoS ONE, 2026)
Psychological wellbeing (PWB) is a vital aspect of healthy aging, encompassing overall functioning, life satisfaction, and the ability to manage life’s challenges. It is shaped by various socio-demographic, financial, and health-related factors. However, evidence on these associations among older adults in Nepal is limited. Accordingly, this study aimed to identify the level of PWB and its associated factors in this population. A cross-sectional analytical study was carried out among 300 older adults attending daycare centers in Kathmandu, Nepal. The respondents were selected using quota sampling based on the daycare centers. Subsequently, face-to-face interviews were conducted to collect data using structured interview schedules covering socio-demographic, financial, and health-related characteristics, as well as the Ryff PWB Scale. The collected data were then entered into Epi data software and analyzed using SPSS version 16. First, descriptive statistics were computed to summarize the sample characteristics and PWB, and subsequently, chi-square tests, and bivariate and multivariate binary logistic regression analyses were performed to examine the associations between the independent variables and PWB. Bivariate analysis shows that sex, marital status, offspring status, literacy status, former employment status, current employment status, pension status, and receipt of the old age allowance (OAA) were significantly associated with PWB. However, in multivariable logistic regression analysis, marital status, literacy status, former employment, and receipt of the OAA were significantly associated with PWB. Married older adults living with a spouse ( AOR = 1.75, 95% CI : 1.02–3.02), literate individuals ( AOR = 2.12, 95% CI : 1.18–3.82), and those with prior employment ( AOR = 3.94, 95% CI : 1.36–11.36) had higher odds of high PWB, with p-value < .05. In contrast, OAA recipients had lower odds of high PWB ( AOR = 0.47, 95% CI : 0.23–0.96, p = .037). Age, sex, and pension status were not significantly associated with PWB in the adjusted model. In conclusion, marital status, literacy status, former employment, and receipt of OAA were the factors associated with PWB. A holistic approach is recommended, including targeted interventions for illiterate older adults; those who are divorced, separated, unmarried, or widowed; those without formal employment history; and OAA recipients. Trial Registration: Not applicable. The authors clarify that this study employed a cross-sectional design, with data collected and analyzed at a single time point, and therefore it does not constitute a clinical trial.